Embracing life after prostate cancer. A male perspective on treatment and rehabilitation. (21st March 2013) - Dieperink, K.B.; Wagner, L.; Hansen, S.; Hansen, O.
<x xml:space="preserve">Abstract</x> This study explores prostate cancer patients' experiences of rehabilitation after radiotherapy with androgen deprivation therapy (ADT). Patients who had completed a multidisciplinary rehabilitation programme with psychosocial support and physiotherapy were interviewed in two focus groups: Group 1 consisted of six men who came to the rehabilitation with their spouses, and Group 2 of seven men who came alone. Meaning condensation was used to analyse the interviews. Radiotherapy was described as full‐time work. Adverse effects due to ADT influencing masculinity and identity were emphasised. The men embraced life with a particular sense of humour. Whether rehabilitation was experienced as useful depended on the health professionals' approach, and on the patients' motivation and effort to contribute to health promotion, and to convert experiences into coping strategies. The supportive role of the spouse was emphasised by several, but some men preferred to handle the process alone. In conclusion, men undergoing ADT should be carefully informed of the consequences. Spousal involvement in rehabilitation must be decided by the patient. The focus group interviews themselves had a positive impact on the men's understanding of their rehabilitation processes. The specific male approach and differences between the needs of female and male cancer patients are important to understand when planning rehabilitation.